2022
DOI: 10.1186/s12951-021-01213-8
|View full text |Cite
|
Sign up to set email alerts
|

3D hanging spheroid plate for high-throughput CAR T cell cytotoxicity assay

Abstract: Background Most high-throughput screening (HTS) systems studying the cytotoxic effect of chimeric antigen receptor (CAR) T cells on tumor cells rely on two-dimensional cell culture that does not recapitulate the tumor microenvironment (TME). Tumor spheroids, however, can recapitulate the TME and have been used for cytotoxicity assays of CAR T cells. But a major obstacle to the use of tumor spheroids for cytotoxicity assays is the difficulty in separating unbound CAR T and dead tumor cells from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
(39 reference statements)
0
30
0
Order By: Relevance
“…This proof-of-concept work provides an example as to how miniaturization through lab-on-chip technologies can be utilized to augment output data when using limited resources. Due to the high selective toxicity of the CAR-T cells and the miniaturization capability of the microfluidic platform used in this work, the E:T ratio could be reduced to far lower values than is typical for conventional in vitro studies, [19,56,57] whilst still eliciting significant cytotoxic effects on the 3D tumour model. Continuous refinement of cell seeding protocols during this work has resulted in the ability to perform over a hundred 3D CAR-T assays (each with 25 technical repeats) using just 1 million cells.…”
Section: Discussionmentioning
confidence: 99%
“…This proof-of-concept work provides an example as to how miniaturization through lab-on-chip technologies can be utilized to augment output data when using limited resources. Due to the high selective toxicity of the CAR-T cells and the miniaturization capability of the microfluidic platform used in this work, the E:T ratio could be reduced to far lower values than is typical for conventional in vitro studies, [19,56,57] whilst still eliciting significant cytotoxic effects on the 3D tumour model. Continuous refinement of cell seeding protocols during this work has resulted in the ability to perform over a hundred 3D CAR-T assays (each with 25 technical repeats) using just 1 million cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite obvious observation of a decrease in size, the direct measurement was inaccurate due to the proximal contact of dead cells and trophozoites. Moreover, the removal of trophozoites and dead SH-SY5Y cells from spheroids allows more accurate measurement of spheroid size, a situation similar to the cytotoxicity assay of CAR T cells [4] (Chen et al, 2022). Taken together, although there is a simple and low-cost way to assess cytotoxicity, improvement of this proposed culture plate form is inevitable.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cells could behave in a way similar to human tissue, including cell-to-cell interactions in all directions, gradient exposure of nutrients and gas, cell polarization, and cell signaling pathways. Studies have reported the physiological relevance of 3D culture regarding cell functions [1], drug response [2] [3], and cell-mediated cytotoxicity [4]. Prospectively, preclinical platforms for modeling human diseases and drug discovery have been changed from the 2D to 3D platform [5] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Screening anti‐cancer drugs, testing cytotoxicity, and analyzing tumour infiltration can be effectively performed using a 3D culture platform, such as tumour spheroids 3 . Moreover, the high‐throughput 3D tumour spheroid screening method might also be a valuable tool for γδ T cell‐based research combined with other anti‐tumour therapies 2 …”
Section: γδ T Cells In Cancer Research and Potential Therapymentioning
confidence: 99%
“…Because of its characteristics, this T cell subset has been studied for its therapeutic efficacy in tumours and virus‐related diseases. Among all the platforms, the novel 3D cell culture system and organ‐on‐chip model are the potential methodologies to establish the microenvironment for infection and tumour studies 2–5 …”
Section: Introduction Of Gamma‐delta T Cellsmentioning
confidence: 99%